Ki Hadjar Dewantara's Philosophy of Education - Harmita; Amelia, Besse Desi; Dupa, Annuri Putri; Inmanora; Supian; Idrus, Ali (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study comprehensively examines Ki Hadjar Dewantara's educational philosophy as an Eastern educational figure who made fundamental contributions to the Indonesian education system. Background Problems: The Indonesian education system has experienced infiltration of Western philosophical determination and value degradation due to emphasis on knowledge transfer over value cultivation, necessitating strengthening of national educational philosophical foundations based on humanization. Novelty: This research integrates literature review from 2015-2025 to holistically map historical background and key philosophical concepts that have not been systematically analyzed, as well as identifying connections with modern educational philosophy streams, particularly essentialism. Research Methods: Systematic literature review method was employed by analyzing 9 selected articles from indexed journals through stages of identification, selection, data extraction, findings synthesis, and critical analysis. Finding/Results: Ki Hadjar Dewantara's educational philosophy is grounded in the concept of independent education emphasizing balance of physical, intellectual, spiritual, and social aspects based on Panca Dharma and Tripusat Pendidikan. The concepts of Trikon, Tri Rahayu, and Among System with the motto “ing ngarsa sung tulada, ing madya mangun karsa, tut wuri handayani” form a practical framework for student-centered education that shares similarities with essentialism yet remains dynamic. Conclusion: Ki Hadjar Dewantara's educational philosophy remains relevant as the foundation of national education in shaping the character of independent, intelligent, and morally noble generations, with implications for the necessity of revitalizing its philosophical values in educational policies to strengthen national educational identity based on local wisdom.